Lower urinary tract symptoms (LUTS) as a clinical feature of lumbar spinal stenosis (LSS): a prospective study with lumbar spine morphometry analysis - Harun Hodzic; Hakija Bečulić; Emir Begagic; Nejla Huseinspahić; Igor Sladojević; Andrej Popov; Rasim Iriškić; Tarik Zulović; Emir Becirovic; Goran Lakičević; Adem Nuhović; Haso Sefo; et al. (Medicinski glasnik, 2025)
Aim: To investigate clinical and morphometric characteristics of patients with lower urinary tract symptoms (LUTS) due to lumbar spinal stenosis (LSS). Methods: This study evaluated LSS patients using clinical assessments of motor, sensory, bladder, and bowel functions, and functional disability scores from the Oswestry Disability Index (ODI) and Swiss Spinal Stenosis Questionnaire (SSSQ). Morphometric analysis included MRI measurements of the anteroposterior diameter of the intervertebral disc and dural sac, and the modified Torg-Pavlov ratio (mTPR), with follow-up re-evaluations at 6 months. Results: Of 159 patients, 49 (30.8%) had LUTS and 110 (69.2%) were in the control group. LUTS patients had a significantly higher prevalence of neurogenic claudication (100% vs. 47.3%; p<0.001), lower back pain (93.9% vs. 77.3%; p=0.011), and lower extremity pain (57.1% vs. 34.5%; p=0.008). The LUTS group also had higher ODI (54.0 vs. 50.0; p=0.019) and SSSQ score (44.0 vs. 34.0; p<0.001). Morphometric analysis showed significantly lower mTPR in LUTS patients (median 0.31 vs. 0.45; p<0.001), with an AUC of 0.704 (95%CI 0.627-0.774). mTPR?0.31 predicted surgical revision within 6 months (OR:3.4, CI: 1.2-9.8), motor deficiency (OR:2.1, 95%CI: 1.4-5.2), and persistent LUTS post-surgery (OR:4.5, 95%CI: 1.1-18.9). mTPR?0.34 was associated with worse follow-up outcome, including increased ODI (?:3.2; 95%CI: 1.1-5.3; p=0.004) and SSSQ score (?:4.8; 95%CI:2.1-7.5). Conclusion: LUTS patients with LSS exhibit more severe symptoms and poorer outcome, with mTPR?0.34 being a predictor of adverse clinical outcome and the need for surgical revision within 6 months.
Keywords: back pain; neurogenic bladder; spinal stenosis; urological manifestations; urinary tract diseases